Novel desmoplakin mutations in familial Carvajal syndrome - YERMAKOVICH, DANAT (Acta Myol, 2018)
Desmoplakin is encoded by DSP gene, whose altered function leads to skin and hair abnormalities, and heart diseases. The whole triad of these traits characterizes the Carvajal syndrome (CS). CS is an autosomal recessive genetic disorder, mapping on chromosome 6q24 and caused by mutations in DSP gene. We report a patient with CS caused by two novel mutations in DSP gene, inherited from his parents, both asymptomatic. The same phenotype was present in his younger sister who showed skin abnormality and woolly hairs. The segregation analysis of the known loci in DSP gene performed by genetic testing, was able to established the trans position of the two mutations (c.6986T > C and c.7123G > C) in the patient and his sister. The first mutation has been inherited from the mother, the other one from the father. The resulting compound heterozygous mutation in the siblings, is likely the cause of the disease.